Rajmund Pietkiewicz, In Search of “the Genuine Word of God”. Reception of the West-European Christian Hebraism the Polish-Lithuanian Commonwealth in the Renaissance (transl. by Monika and Jacek Szela, Göttingen: Vandenhoeck & Ruprecht 2020). - Pilarczyk, Krzysztof (The Biblical Annals, 2021)
Book Review: Rajmund Pietkiewicz, In Search of “the Genuine Word of God”. Reception of the West-European Christian Hebraism the Polish-Lithuanian Commonwealth in the Renaissance (transl. by Monika and Jacek Szela, Göttingen: Vandenhoeck & Ruprecht 2020).